1985
DOI: 10.1177/00220345850640021701
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Acidurance of Streptococcal Growth and Glycolysis by Fluoride and Gramicidin

Abstract: The acidurance of glycolysis by intact cells of Streptococcus mutans GS-5, Streptococcus salivarius ATCC 25925, and Streptococcus sanguis NCTC 10904 was found to be highly dependent on membrane functions affected by gramicidin, which increases the proton permeability of cell membranes. Plots of % glucose utilized during two hours against suspension pH values for cells suspended in 100 mM phosphate buffer plus 1 mM MgCl2 plus 13.9 mM glucose indicated, for 50% glucose utilization, pH values of 5.0 for S. mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 13 publications
4
44
0
Order By: Relevance
“…Thus, the loss of ManL dramatically impacts glycolytic rates when cells are grown in limiting glucose. Also of note, the terminal pH achieved in the pH drop assay is strongly correlated with acid tolerance (17,41,42), with the lower pH being associated with greater acid tolerance. The fact that cells that lacked ManL and that were limited for glucose could not achieve as low a terminal pH as the wild-type strain grown under the same conditions implicates ManL as a potential contributor to or regulator of acid tolerance.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the loss of ManL dramatically impacts glycolytic rates when cells are grown in limiting glucose. Also of note, the terminal pH achieved in the pH drop assay is strongly correlated with acid tolerance (17,41,42), with the lower pH being associated with greater acid tolerance. The fact that cells that lacked ManL and that were limited for glucose could not achieve as low a terminal pH as the wild-type strain grown under the same conditions implicates ManL as a potential contributor to or regulator of acid tolerance.…”
Section: Resultsmentioning
confidence: 97%
“…Rapid fermentation of sugars by S. mutans can cause a substantial drop in the pH of oral biofilms, from neutral pH to values well below 5 (16). The acidic environment created by carbohydrate fermentation favors the growth of S. mutans over that of health-associated, acid-sensitive commensal organisms, because S. mutans is well adapted to survive and continues to metabolize carbohydrates at low pH (17).…”
mentioning
confidence: 99%
“…The enhanced capacity of cells grown with glucose alone or a combination of glucose and GlcNAc to lower the pH when exogenous glucose was provided may be explained as follows. Previous studies have demonstrated that exposure to a moderately acidic environment (e.g., pH 5.5 for 2 h) is correlated with enhanced acid tolerance, attributable to the induction of the adaptive acid tolerance response (ATR) (60,(84)(85)(86)(87). Two hallmarks of induction of the ATR in S. mutans are more rapid metabolism of carbohydrate and attainment of a lower final pH in pH drop assays.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of fluoride release from the coating material. Fluoride can reduce acid production by S. mutans through a number of mechanisms 50) , including inhibition of the glycolytic enzyme enolase 51,52) and the proton-extruding ATPase 53,54) . The reduced drop of pH on the surface of PRG Barrier Coat could also be related to interference with other intracellular or plaque-associated enzymes in S. mutans, such as acid phosphatase, pyrophosphatase, peroxidase and catalase by released fluoride 55) .…”
mentioning
confidence: 99%